Pengoptimalan Pengelolaan Keuangan Pesantren: Integrasi Nilai-Nilai Islam Dalam Akuntansi Syariah Untuk Pengurus Pesantren PPM. Al Jawi Surabaya - Fadilah, Elvira Nurul; Amanda, Ericca Dhea; Nabilla, Hania Rifdah; Lathifah, Iif Ainul; Mukaromah, Lailatul; Ningrum, Chofifah Ayu Widya; Yudhanti, Ashari Lintang (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
The rapid development of science and technology has also influenced the field of accounting, including the application of sharia accounting in non-profit entities such as Islamic boarding schools. Islamic boarding schools in Indonesia continue to grow every year, but many do not understand the concept of Islamic economics and sharia accounting in depth. This activity aims to provide education to the management of the Al Jawi Islamic Boarding School in Surabaya regarding Islamic economics, the benefits of financial reports, and the application of sharia contracts in accounting. The implementation method includes education through training and interactive discussions as well as in-depth interviews with the boarding school management. The results of the activity showed an increase in the understanding of the boarding school management regarding the principles of Islamic economics and sharia accounting. Positive responses were seen from the enthusiasm of the participants in discussing and asking questions. The evaluation of the activity revealed that the boarding school management had begun to carry out simple financial records, although the application of more complex accounting according to PSAK Syariah still requires further assistance.